Aceh’s Government Role Implementation in Overcoming Emergency of Natural Disaster and Outbreak of Diseases - M. Gaussyah; Mirja Fauzul Hamdi; Ahmad Mirza Safwandy (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2022)
This article addresses how to implement the Government of Aceh's role in resolving emergency circumstances resulting from natural and man-made disasters. As a strategy for addressing the post-disaster effects in Aceh, it is essential to implement regulations and policies that anticipate emergency circumstances and disaster emergencies. Aceh has a high risk of natural and man-made disasters, necessitating the active participation of the Aceh government and the entire community in anticipating and mitigating these risks. The Government of Aceh must be able to carry out its responsibilities successfully and efficiently, particularly in emergency situations. This can be achieved through the development of swift, accurate, solution-oriented, and responsive legislation. Decentralization of affairs and authority from the centre to the regions to formulate regulations and policies according to regional interests are supporting factors for the Aceh Government's role in dealing with disaster emergencies, while the absence of regulations that give direct authority to the Aceh Government to compile practical regulations and policies in dealing with emergency situations are inhibiting factors.